2011
DOI: 10.1136/bcr.09.2011.4790
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic weight loss associated with commencing clozapine

Abstract: The authors report the case of a 44-year-old man with a long history of chronic enduring schizophrenia who experienced dramatic weight loss after commencing treatment with clozapine, an antipsychotic medication characteristically associated with the greatest degree of weight gain among medical treatments for schizophrenia. He was obese with a body mass index (BMI) of 41.5 kg/m(2), but after commencing clozapine therapy he experienced an improvement in psychotic symptoms and 40% loss of his body weight attained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They hypothesised that improvement in negative symptoms was the main drive behind loss of weight 21. This line of reason was emphasised in the case reported by Lally and McDonald22 when significant improvement in motivation and engagement in regular exercise were produced about by initiation on clozapine. They noted a subsequent striking drop in BMI from 41.5 to 24.8 kg/m 2 .…”
Section: Discussionmentioning
confidence: 96%
“…They hypothesised that improvement in negative symptoms was the main drive behind loss of weight 21. This line of reason was emphasised in the case reported by Lally and McDonald22 when significant improvement in motivation and engagement in regular exercise were produced about by initiation on clozapine. They noted a subsequent striking drop in BMI from 41.5 to 24.8 kg/m 2 .…”
Section: Discussionmentioning
confidence: 96%
“…It is also possible that the decline in HbA1c levels observed in the present study was due to cognitive improvements. For example, CLZ treatment has shown an association with weight loss (Thomas et al 2009;Hanwella et al 2010;Appiani et al 2011;Lally and McDonald 2011;Webster and Ingram 2013;Tungaraza 2016) and some case reports have indicated that improvements in cognitive func-tion due to CLZ treatment increased patients' interest in diet and exercise, which resulted in decreased body weight (Appiani et al 2011;Lally and McDonald 2011). Because psychopathologies and cognitive function were not evaluated in the present study, further studies will be necessary to clarify the correlations between improvements in psychotic symptoms and/or cognitive function and HbA1c levels after the initiation of CLZ.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation given as to the cause of weight loss varied between cases. In three cases [Lally and McDonald, 2011; Appiani et al , 2011; Webster and Ingram, 2013], weight loss was as a result of improved mental state, better side-effect management and engagement in diet and exercise. In the three cases reported by Hanwella and colleagues, weight loss was attributable purely to taking clozapine [Hanwella et al .…”
Section: Discussionmentioning
confidence: 99%
“…Management of antipsychotic-induced weight needs to include a number of strands such as lifestyle changes, cognitive behavioural therapy, change to antipsychotics that are less likely to cause weight gain and adding compounds known to induce weight loss [Kwon et al 2006; Khazaal et al 2007; Raja, 2011; Werneke et al 2013]. Lifestyle modification was possible in two cases [Lally and McDonald. 2011; Appiani, 2011].…”
Section: Weight Managementmentioning
confidence: 99%